2014
DOI: 10.1530/rep-13-0393
|View full text |Cite
|
Sign up to set email alerts
|

Capacitation in the presence of methyl-β-cyclodextrin results in enhanced zona pellucida-binding ability of stallion spermatozoa

Abstract: While IVF has been widely successful in many domesticated species, the development of a robust IVF system for the horse remains an elusive and highly valued goal. A major impediment to the development of equine IVF is the fact that optimised conditions for the capacitation of equine spermatozoa are yet to be developed. Conversely, it is known that stallion spermatozoa are particularly susceptible to damage arising as a consequence of capacitation-like changes induced prematurely in response to semen handling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 58 publications
(64 reference statements)
7
35
0
Order By: Relevance
“…The only treatment that consistently induced a significant decrease in sperm cholesterol content was MW with MbCD at 1 and 3 mM (Figs 1 and 2). Incubation with MbCD has been shown to extract cholesterol from sperm plasmalemma of different mammalian species (Visconti et al 1999c, Bromfield et al 2014. Consistent with our findings, Boerke et al (2013) found in porcine sperm that cholesterol efflux mediated by MbCD is ROS independent, unlike BSAmediated cholesterol extraction, which requires the Figure 8 Number of equine sperm bound to bovine ZP.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The only treatment that consistently induced a significant decrease in sperm cholesterol content was MW with MbCD at 1 and 3 mM (Figs 1 and 2). Incubation with MbCD has been shown to extract cholesterol from sperm plasmalemma of different mammalian species (Visconti et al 1999c, Bromfield et al 2014. Consistent with our findings, Boerke et al (2013) found in porcine sperm that cholesterol efflux mediated by MbCD is ROS independent, unlike BSAmediated cholesterol extraction, which requires the Figure 8 Number of equine sperm bound to bovine ZP.…”
Section: Discussionsupporting
confidence: 88%
“…An increase in PYassociated with treatment with MbCD was reported in equine sperm, but this was examined only in media containing activators of the cAMP-PKA pathway (Pommer et al 2003); such activators essentially bypass the dependence of PY on cholesterol efflux (Visconti et al 1995). Similarly, Bromfield et al (2014) have recently evaluated factors affecting cholesterol reorganization patterns and PY in equine sperm, but essentially only in the presence of pentoxifylline and dibutyryl cAMP. Incubation of equine sperm with MbCD in the basal medium (not containing stimulators of the cAMP-PKA pathway) promoted changes in measures of membrane fluidity and cholesterol organization, but did not significantly increase PY; remarkably, the effects of BSA on these parameters in the basal medium were not reported (Bromfield et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were extended in utero by Brown & Senger (1982) who placed rabbit spermatozoa into the uterine lumen and noted significant agglutination of motile spermatozoa. Similar effects have been reported in the stallion with the use of BSA under capacitating conditions, so it is commonly substituted with polyvinyl alcohol (PVA; Bromfield et al 2014).…”
Section: Introductionmentioning
confidence: 61%
“…the stallion; (Bromfield et al 2014)). There are considerable differences in sperm morphology and physiology across mammalian species, so it is not surprising that distinct species-specific capacitation phenomena also occur.…”
Section: Introductionmentioning
confidence: 99%